Cover crop and phosphorus fertilizer management impacts on surface water quality from a no-till corn-soybean rotation. (1st January 2022) - Carver, R. Elliott; Nelson, Nathan O.; Roozeboom, Kraig L.; Kluitenberg, Gerard J.; Tomlinson, Peter J.; Kang, Qing; Abel, David S.
Abstract: Best management practices that reduce potential phosphorus (P) loss and provide flexibility in P fertilizer management are needed to help producers protect water quality while maintaining crop yield. This study examined the impacts of P fertilizer management (no P, fall broadcast P, and spring injected P) and cover crop use on annual concentrations and loads of sediment, total P, and dissolved reactive P (DRP) in edge-of-field runoff from a no-till corn ( Zea mays )-soybean ( Glycine max ) rotation in the Central Great Plains, USA, from September 2015 through September 2019. The spring injected P fertilizer treatment generally had 19% less total P and 33% less DRP loss compared to the fall broadcast treatment, confirming the importance of P fertilizer management as a practice for reducing P loss. The addition of a cover crop had an inconsistent effect on total P loss, with no effect in 2016 and 2017, increasing loss in 2018 by 56%, and decreasing it in 2019 by 40%. The inconsistent impact of cover crops on total P loss was related to cover crop effects on sediment loss. Although cover crop impacts on total P losses were inconsistent, the addition of a cover crop increased DRP loss in three of four years. Cover crop use consistently reduced sediment loss, with greater sediment reduction when P fertilizer was applied. Results from this study highlight the benefit of cover crops for reducing sediment loss and the continued need for proper fertilizer management to reduce P loss from agricultural fields. Highlights: Cover crops reduced sediment loss and total P loss when sediment loss was high. Cover crops increased dissolved reactive P loss in years with little sediment loss. Subsurface placement of P fertilizer is a best management practice to reduce P loss. P fertilizer management is key to protect water quality even with cover crop systems. Cover crops are a site-specific management tool to reduce sediment and total P loss.